Hubungan Volume Lalu Lintas Dengan Kapasitas Jalan di Jalan Veteran Banjarmasin - Hadi Gunawan (Universitas Lambung Mangkurat, 2007)
The areas on the Veteran street, it’s has complect for people whos as natives following on the times and its economics developing with any concequencies of business zones. Therefor it’s actually the magnifaceint of orders. The traffic jumps had been coming onVeteran street, on those conditions so that it’s quite interesting to be reseeched through on correlation to alls of resulting due to of it.For any evaluations it has must be worked uses by Indonesia Highway Capacity Manual (MKJI,1997), by infutable geometric conditions, traffic conditions, environmental conditions, base capacity, city size adjustment factor, road environment type, side friction, unmotorised vehicles adjustment factor and actual capcity, it’s metode uses to statistic analise regressions (Kennedy, J.B dan Neville, A.M, 1995) the conjuctions those accursedly with dereclly for Merdeka Bright to Kuripan Market street is linier with equition Y = -1,628X + 4842,9 with counts r = -0,897 (the correlation are variabel of negatives and it is strongly), from Kuripan Market dereclly to Merdeka Bright is linier with equition Y = -0,4135X + 2674,9 with counts r = -0,897 (the correlation are variabel of negatives and it is strongly) and for the through coupces of street is linier with equition Y = Y = -0,466X + 5505,3 with counts r = -0,912 (the correlation are variabel of negatives and it is strongly).